Alternatives to Neoliberal Globalization Studies in the Political Economy of Institutions and Late Development - Lo, D. (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2012)
This book seeks to clarify the positive and negative lessons in the experiences of late development under neoliberal globalization. Dic Lo explores competing theories, with a view to constructing an alternative synthesis that transcends neoliberalism, placing greater emphasis on solidarity and humanistic development.